Tudor tells about new twists in the story tale of SMURFs - Qureshi, M Z; Jabeen, S; Butt, G; Aslam, A; Naqvi, S K; Attar, R; Tabassum, S; Nasir, M; Farooqi, A A (Cellular and Molecular Biology, 2016)
Smad ubiquitin regulatory factors (SMURFS) belong to the HECT- family of E3 ubiquitin ligases. This family has two members, SMURF1 and SMURF2. SMURFs have emerged as well studied negative regulators of TGF induced intracellular signaling. However, increasingly it is being realized that SMURFs tactfully modulate an array of proteins in different cancers. This review sets spotlight on how SMURF1 and SMURF2 communicate with effectors of different signaling pathways during the multistep progression to cancer. We also summarize how microRNAs (miRNAs) effectively control SMURFs in different cancers. Role of SMURFs is context dependent in different cancers and better concepts related to miRNA regulation of SMURFs in different stages and steps of cancer will be helpful in efficient translation of laboratory findings to clinic.